Metabolic disorders as a factor in pathogenesis of infectious diseases in cattle - A. D. Alekseev (Ветеринария сегодня)
An important factor affecting the performance of cattle is the satisfaction of animal needs in nutrients, macro- and microelements. High-yielding dairy cows with intense metabolism are especially sensitive to errors in feeding practices, because even minor nutritional or mineral deficiencies cause metabolic disorders leading to immunodeficiency conditions, reduced resistance to infectious agents and raised sensitivity to infections with pathogenic and opportunistic microorganisms. Besides some infections, for example acute respiratory diseases, also result in metabolic disorders, immunosuppression, decrease in the overall resistance of the organism and ultimately in mixed infections. All this is the reason for low efficacy of vaccination against major infectious diseases. The paper presents the results of testing of plant tissue product «Vidoral», developed by the FSBEI HE Ural SAU for prevention of immunodeficiency conditions in cattle, caused by different factors. The product was injected subcutaneously at a dose of 0.025 ml/kg of live weight to cows in late gestation and calves showing mild anemia, low red blood cells counts, leukocytosis, high lymphocyte and monocyte counts and elevated erythrocyte sedimentation rate, which suggest inflammatory processes in the animal body. Fourteen days post injection blood was collected for hematological and biochemical testing. It was demonstrated that the product restores the animal metabolism, improves hematopoiesis and reduces inflammation. It was established that injection of «Vidoral» in combination with vaccination against infectious rhinotracheitis, viral diarrhea, infection with respiratory syncytial virus and parainfluenza-3 virus induced generation of specific antibodies against the abovementioned infections.